2008
DOI: 10.1590/s1516-35982008000500014
|View full text |Cite
|
Sign up to set email alerts
|

Restrição alimentar qualitativa para suínos com elevado peso de abate

Abstract: RESUMO -Foram utilizados 60 suínos machos castrados (89,1 ± 4,2 kg) para avaliar o uso de níveis (0, 5, 10, 15 e 20%) de restrição qualitativa, resultando em valores de 3. 407, 3.240, 3.060, 2.890 e 2.720 kcal de energia digestível por quilo de ração. Dez animais foram abatidos no início do experimento para determinação da composição corporal inicial, enquanto os demais foram alimentados com as dietas experimentais até atingirem 128 kg. Utilizou-se o delineamento em blocos casualizados para controle das dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 10 publications
1
8
0
6
Order By: Relevance
“…Inclusion of citrus pulp to diets did not decrease the blood triacylglycerol content, as the highest reduction of energy was 8.5%, which was observed with the use of Cp30 diet. However, Fraga et al (2008) observed a negative linear trend on triacylglycerol levels as the energy of diet drop up to 20% with the inclusion of rice hulls. For the total cholesterol content, a quadratic trend was observed, and the highest predicted level was reached at 22.63% of citrus pulp inclusion.…”
Section: Trialmentioning
confidence: 89%
“…Inclusion of citrus pulp to diets did not decrease the blood triacylglycerol content, as the highest reduction of energy was 8.5%, which was observed with the use of Cp30 diet. However, Fraga et al (2008) observed a negative linear trend on triacylglycerol levels as the energy of diet drop up to 20% with the inclusion of rice hulls. For the total cholesterol content, a quadratic trend was observed, and the highest predicted level was reached at 22.63% of citrus pulp inclusion.…”
Section: Trialmentioning
confidence: 89%
“…Watanabe et al (2010) reported that the use of citrus pulp in the diet modified the colour parameters, and observed a linear reduction in the L*, a* and b* values as the dietary levels of citrus pulp increased from 10 to 30%. Fraga et al (2008) also reported a reduction in the a* and b* values as a result of the inclusion of rice hull in diets; these authors indicated that this effect is probably due to a reduction in dietary pigments due to the low level of corn in the diet.…”
Section: Meat Quality Traitsmentioning
confidence: 96%
“…While Fraga et al (2008) did not report any reduction in the carcass yield in response to the inclusion of 19% of rice hull in the diet of swine slaughtered at a live weight of 130 kg, Scipione et al (1991) reported a significant reduction in carcass yield in pigs fed with sugar beet pulp silage and slaughtered at 144 kg. Paiva-Martins et al (2009) reported that the use of 5 or 10% of olive leaves in the diet decreased the carcass weight and yield, the back fat thickness and the area of the Longissimus muscle.…”
Section: Semimembranosusmentioning
confidence: 98%
“…Soma-se, ainda, o fato de que o custo da polpa cítrica foi relativamente alto no momento de aquisição, fato agravado com o aumento do número de dias necessários para os animais atingirem 130kg, quando a inclusão foi de 30%. Fraga (2005) ponderou que, em programas de restrição alimentar qualitativa, quanto maior a relação entre os preços do milho e do ingrediente alternativo, menor será o custo para se atingir o peso de abate acima de 120kg, ressaltando ainda a importância em utilizar resíduos da indústria alimentícia de baixo valor comercial.…”
Section: Methodsunclassified